2005
DOI: 10.1111/j.1365-2958.2005.04496.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Bacillus catabolite control protein CcpA interacts with RNA polymerase to inhibit transcription

Abstract: SummaryBacillus catabolite control protein (CcpA) mediates carbon catabolite repression (CCR) by controlling expression of catabolite responsive (CR) genes or operons through interaction with catabolite responsive elements ( cre s) located within or outside of CR promoters. Here, we investigated how CcpA inhibits the transcription of CR promoters in vitro . CcpA has different affinities for different cre s, but this does not correlate with its ability to inhibit transcription. In the amyE promoter, which overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…al (28). This K d was lower than for those calculated for CcpA binding at other cre sites, including ccpC (12 nM) (26), amyE (28 nM), gnt (100 nM), and xyl (330 nM) (29). Other cre sites that bind CcpA without coeffectors but for which no K d was reported include the cre2 site of ackA (41) and the cre site of rocG (3).…”
Section: Discussionmentioning
confidence: 58%
“…al (28). This K d was lower than for those calculated for CcpA binding at other cre sites, including ccpC (12 nM) (26), amyE (28 nM), gnt (100 nM), and xyl (330 nM) (29). Other cre sites that bind CcpA without coeffectors but for which no K d was reported include the cre2 site of ackA (41) and the cre site of rocG (3).…”
Section: Discussionmentioning
confidence: 58%
“…It was therefore concluded that NADP(H) does not function as a corepressor by enhancing the binding of CcpA to the cre but, rather, that it allows CcpA to inhibit the transcription machinery, thus leading to reduced amyE expression (404). CcpA has been proposed to directly interact with and to inhibit RNA polymerase, and NADP/NADPH was thought to stimulate the interaction of CcpA with RNA polymerase (406). The suggested role of NADP and NADPH cannot be related to the redox state of the cells, as both molecules were similarly efficient in the stimulation of CcpA-mediated inhibition of amyE expression, while NAD and NADH had no effect.…”
Section: P-ser-hpr Functions As a Catabolite Corepressormentioning
confidence: 99%
“…At 8 and 16 min after 29 infection, the most downregulated pathways were related to the utilization of specific carbon sources of bacteria, including ribose, inositol, sucrose, lichenan, starch, trehalose, or galacturonate ( Table 2). In fact, 39 of the 55 genes that are downregulated after viral infection are members of operons repressed by the catabolite control protein A (CcpA) ( Table 2), a DNAbinding protein of the LacI/GalR family of transcriptional regulators (38,39). Moreover, most of these CcpA-regulated genes (82%) contain high-affinity binding sequences for CcpA called cre (catabolite responsive elements).…”
Section: Resultsmentioning
confidence: 99%